Paralympic athletes’ perspective of doping self-regulatory efficacy in Nigeria - Adegbesan, Olufemi A; Akingbola, Titilola S; Adeniyi, Ade F; Ayorinde, John O; Jaiyeoba, Oluwatoyin M; Olowoleni, Victor B (Journal Sport Area, 2024)
Background Problems: With the high demands of sports and the crave for success despite diminishing strength with ageing in the presence of disability, athletes are tempted to contravene the ADRV. Research Objectives: The study aimed to study paralympic athletes’ perspective of doping self-regulatory efficacy in Nigeria. Methods: Descriptive survey design was adopted for the study. A 13-item validated questionnaire (α= .74) was employed to collect data for the study. One-hundred and twenty-four male (81) and female (43) elite para-athletes (mean= 23.15 years, ±3.65) voluntarily participated in the study. ANOVA, PPMC, and Cramer’s V Chi-Square Coefficient Contingency were used to determine the relationship and difference across age, gender and sport type and the extent of the para-athletes’ likelihood to dope and confidence to avoid banned substances, respectively. Findings and Results: It indicated a significant effect of age on likelihood to dope at the p < 0.05 for all conditions (F (1, 123) = 45.84, p = 0.000). Therefore, the null hypothesis was rejected. Findings indicated no significance across gender (0.091, p > 0.05), sport (0.280, p > 0.05), and age (0.263, p > 0.05) on the likelihood to dope. Although, significant among older (0.022), female (0.024) para-athletes. Cramer’s V indicated a strong association when drugs would give immediate fitness (ɸ = 0.217), (ɸ = 0.243), and (ɸ = 0.263) across age, gender, and sport type respectively. Conclusion:  It is concluded among others that the para-athletes showed high self-efficacy and low likelihood to dope even in the presence of stressors. However, the ever-pressing need for the athlete’s body longing need for nutrition, oxygen, rest and staying in shape and top form for competing increased the possibility to use a banned drugs for your injury recovery among some older athletes. Psychological interventions are suggested combat the likelihood to dope given the experience levels or psychological dispositions of athletes.